2017
DOI: 10.1136/archdischild-2017-312927
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ knowledge and attitudes to sudden infant death syndrome risk reduction messages: results from a UK survey

Abstract: ObjectiveTo investigate mothers’ knowledge of reducing the risks for sudden infant death syndrome (SIDS) and attitudes towards safer sleep practices.Design and settingA cross-sectional survey was carried out in deprived areas of Bristol, UK. Recruitment took place in 2014 at local health visitor-led baby clinics.ParticipantsOf 432 mothers approached, 400 (93%) completed the face-to-face survey. Participants with infants at ‘higher’ risk of SIDS (using an algorithm based on a previous observational study) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…A 19-item measure of educator knowledge, beliefs and confidence regarding infant sleep was developed (online supplementary table 1) modelled from that used by Pease 15. Seven items assessed educator knowledge, six items assessed educator beliefs and four items assessed educator confidence.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A 19-item measure of educator knowledge, beliefs and confidence regarding infant sleep was developed (online supplementary table 1) modelled from that used by Pease 15. Seven items assessed educator knowledge, six items assessed educator beliefs and four items assessed educator confidence.…”
Section: Methodsmentioning
confidence: 99%
“…Other factors identified as risks (eg, hazardous cosleeping) or protections (eg, breastfeeding) are less salient in the childcare context, although it is noted that childcare services are significant sites for public health promotion and parent education 14. In home settings, there is evidence that many families do not follow safe sleeping guidelines, do not follow all guidelines or do not follow them all of the time 15–18. For example, placing a baby to sleep in a non-supine position (front or side placement) has been consistently shown as a significant risk factor for sleep-related infant death1 and, since the 1990s, a key focus of related public health campaigns 19.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent survey of higher-risk families found that as few as one third identified back sleeping as a risk reduction strategy for SIDS (Pease et al, 2018), and related qualitative work found a lack of understanding about why or how sleeping position is related to SIDS (Pease et al, 2017). Future interventions in this area should, therefore, consider effective ways to improve understanding as well as knowledge.…”
Section: Infant Sleeping Positionmentioning
confidence: 99%